2013
DOI: 10.1055/s-0033-1334460
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Perinatal Outcomes Associated with Acinetobacter baumannii Infection

Abstract: Objective To determine perinatal and pregnancy outcomes of Acinetobacter baumannii infection using clinicopathologic material from pregnant women, neonates, and perinatal postmortem examinations with positive cultures.Study Design This is a retrospective record review with placental and postmortem examination.Results During a 5-year period, 40 positive cultures were found. Three pregnancies with positive cultures close in the peripartum period were all associated with adverse outcomes including spontaneous abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is unlikely that UTI leads to PE (Loh et al, 2007). He and colleagues believe that UTI increases pyelonephritis, cystitis and kidney problemsin pregnancy and patients are at risk of increased blood pressure and PE (He et al, 2013). However, in another study conducted in Croatia, it was shown that treatment of UTI in pregnant women with insulin-dependent diabetes mellitus (and not in healthy pregnant women) reduces the chance of acute pyelonephritis and PE (Drazancićet al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that UTI leads to PE (Loh et al, 2007). He and colleagues believe that UTI increases pyelonephritis, cystitis and kidney problemsin pregnancy and patients are at risk of increased blood pressure and PE (He et al, 2013). However, in another study conducted in Croatia, it was shown that treatment of UTI in pregnant women with insulin-dependent diabetes mellitus (and not in healthy pregnant women) reduces the chance of acute pyelonephritis and PE (Drazancićet al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…CorrZIDF Acinetobacter Acinetobacter infection in adverse pregnancy and perinatal outcomes [31,32] Aerococcus Low abundance in preterms [33] Atopobium High relative abundance of Atopobium vaginae at the midtrimester was highly predictive of preterm birth [34] Bacteroides Abundance reduction in Bacteroides in women who delivered preterm [35,36] Brevibacterium Occasionally found in the placenta, considered as contaminants [37] Campylobacter Associated with an increased risk of spontaneous abortion, stillbirth, and preterm delivery [38] Fusobacterium Associated with preterm birth and has been isolated from the amniotic fluid, placenta, and chorioamnionic membranes of women delivering prematurely [39] Mobiluncus For women with a prior preterm delivery, high level of Mobiluncus significantly indicate a spontaneous preterm delivery [40] Oligella Mostly found as a commensal organism of the human genitourinary tract, which is also the main infection site [41] Peptostreptococcus Pregnant women with Bacterial vaginosis including Peptostreptococcus and other bacteria have increased risk of preterm labor and preterm premature rupture of membranes.…”
Section: Genus Relevance Referencementioning
confidence: 99%